Results of Breast Conservation Therapy for Breast Cancer at Chonburi Cancer Center - โตวณะบุตร ช่อแก้ว; ธนบดี จิตราพร; ตั๊นเจริญ ขวัญใจ (Journal of Thai Association of Radiation Oncology, 2012)
Introduction : The treatment of early- stage breast cancer using breast conservation therapy has been widely accepted to be as effective as Modifi ed radical mastectomy. Breast conservation therapy has been used at Chonburi cancer center since 1998. This study reported the outcomes of breast conservation therapy at Chonburi Cancer Center. Objective : To evaluate the outcomes of breast conservation therapy at Chonburi Cancer Center in terms of survival rate, pattern of failure, cosmetic results and late complications. Materials and Methods : A descriptive study using retrospective data of patients with breast cancer who received breast conservation therapy at Chonburi Cancer Center from September 1998 to December 2010 was conducted. The patient information from medical record and the patient treatment history of Department of radiation oncology were reviewed and extracted using data entry form. Evaluation of treatments and late complications were performed by physicians. Data analysis was performed using descriptive statistics. Overall survival and disease free survival rates were calculated by Kaplan-Meier survival function. Results: Forty two female patients with age ranged from 20-62 years at mean age of 44.5+ 8.09 years received breast conservation therapy from September 1998 to December 2010. The follow up time ranged from 0.54 to 13 years with median at 3.2 years revealed that 5-yr disease survival and overall survival had similar rates at 90.62%. Nineteen percent of patients (8 cases) had excellent cosmetic result, 31% (13 cases) had good cosmetic results and 28.6% (12 cases) had fair results while 7.1% (3 cases) had poor results. Late complications were documented among these patients, 21.4% (9 cases) had subcutaneous tissue late complication at level 3. Two patients (4.8%) had local recurrences and 1 patient (2.4%) had distant metastasis. Conclusions: A retrospective study on breast conservation therapy for breast cancer at Chonburi Cancer Center revealed high overall survival rate, low recurrence rate and satisfactory cosmetic results. Subcutaneous tissue complication rate caused by the treatment was still considerably high. Breast conservation therapy followed by radiation can be used to replace modifi ed radical mastectomy at Chonburi Cancer Center. However, additional studies regarding factors affecting late complications and cosmetic results should be performed to improve treatment strategies.